Analisis Pemanfaatan Program Deteksi Dini Kanker Serviks dengan IVA oleh Peserta JKN-KIS - Nur An Nisaa; Antono Suryoputro; Aditya Kusumawati (Media Kesehatan Masyarakat Indonesia, 2019)
The national program for early detection of cervical cancer by VIA has been supported by BPJS Kesehatan,but its utilization remains low. The utilization of VIA in Semarang City was only 1.7% in 2017. The purpose of thisstudy was to analyze the factors related to the utilization of VIA by JKN-KIS participants. This study used quantitativemethods with cross-sectional approach. The research location was in Banyumanik Subdistrict with 100 womenof childbearing age, active participants of JKN-KIS who were married. Data analysis used Chi-square and multiplelogistic regression. The results showed that the majority of respondents had not utilized VIA (87%), had lessknowledge (56%), unfavorable attitude (57%), good access (55%), less social support (56%), low perceived vulnerability(56%), high perceived severity (52%), low perceived benefits (58%), and high perceived barriers (61%).Variables related to the utilization of VIA by JKN-KIS participants are knowledge (p=0,000), attitude (p=0,000),social support (p=0,000), perceived vulnerability (p=0,002), perceived benefits (p=0.006), and perceived barriers(p=0.003). While the most influential factor is attitude (p=0.04; OR=9.872). Thus, women with an unfavorableattitude has a probability of 9,872 times to not conduct a VIA test.